Effect of Transcranial Direct Current Stimulation Combined With Xbox-Kinect Game Experience on Upper Limb Movement in Down Syndrome: A Case Report - Lopes, Jamile Benite Palma; Miziara, Isabela Marques; Galli, Manuela; Cimolin, Veronica; Oliveira, Claudia Santos (Frontiers in Bioengineering and Biotechnology, 2020)
Transcranial direct current stimulation (TDCS) has been widely studied to determine local synaptic efficacy and modulate of the electrical activity of the cortex in patients with neurological disorders. The scientific community has sought to combine this type of stimulation with well-established therapeutic modalities, such as motor training involving virtual reality, which has demonstrated promising results in the scientific literature. Thus, the aim of the present study was to determine whether TDCS can enhance the effects of upper limb motor training in children with Down syndrome through a case report involving an eight-year old child (cognitive age: five years – based on the Wechsler Intelligence Scale for Children) with a diagnosis of Down syndrome. The evaluations consisted of the three-dimensional analysis of the upper limb during a reaching task performed before, after and one month after the intervention. The intervention protocol involved ten 20-minute sessions of TDCS over the primary motor cortex at an intensity of 1 mA during virtual reality training involving an upper limb motor task. This study was conducted at the Movement Analysis Lab of Nove de Julho University (São Paulo, Brazil) following approval from the local ethics committee (certificate number: 1.540.113) and is registered with the Brazilian Clinical Trials Registry (N° RBR3PHPXB). The results were analyzed statistically, with a p-value ≤ 0.05 considered indicative of statistical significance. With the proposed protocol, TDCS is believed to optimize motor training, leading to modifications in kinematic variables during the execution of a motor task. The present case report offers preliminary data from a protocol study and the results confirm the notion that anodal TDCS combined with upper limb motor training leads to improvements in different kinematic variables.